Buckdancer's choice : poems - Dickey, James (Wesleyan poetry program., 1965)
Whoever looks to a new book by James Dickey for further work in an established mode, or for mere novelty, is going to be disappointed. But those who seek instead a true widening of the horizons of meaning, coupled with a sure-handed mastery of the craft of poetry, will find this latest collection satisfying indeed. Here is a man who matches superb gifts with a truly subtle imagination, into whose depths he is courageously traveling--pioneering--in exploratory penetrations into areas of life that are too often evaded or denied. "The Firebombing," "Slave Quarters," "The Fiend"--These poems, with the others that comprise the present volume, show a mature and original poet at his finest